Cells alignment and accumulation using acoustic nozzle for 3D printing - Sriphutkiat, Yannapol (2018)
Arrangement or patterning of microparticles/cells would enhance the efficiency, performance, and function of the printed construct. This could be utilized in various applications such as fibers reinforced polymer matrix, hydrogel scaffold, and 3D printed biological samples. Magnetic manipulation and dielectrophoresis have some drawbacks, such as time-consuming and only valid for samples with specific physical properties. Here, acoustic manipulation of microparticles in the cylindrical glass nozzle is proposed to produce a structural vibration at the specific resonant frequency. With the acoustic excitation, microparticles were accumulated at the center of the nozzle and consequently printed construct at the fundamental frequency of 871 kHz. The distribution of microparticles fits well with a Gaussian distribution. In addition, C2C12 cells were also patterned by the acoustic waves inside the cylindrical glass tube and in the printed hydrogel construct. Overall, the proposed acoustic approach is able to accumulate the microparticles and biological cells in the printed construct at a low cost, easy configuration, low power, and high biocompatibility.